Pengembangan Chip Kertas untuk Deteksi Chronic Kidney Disease secara Dini (Development of Paper Based Chip for The Early Detection of Chronic Kidney Disease) - Dwi Citra Nur Utami; Bambang Kuswandi; Lestyo Wulandari (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Chronic kidney disease (CKD) is a condition of kidney which cannot perform its function normally, and expected to increase every year. Paper based chip was used in this case made by immobilized picric acid for creatinine detection, tetrabromophenol blue for protein detection, and bromothymol blue and methyl red for pH detection, on “whatman” filter paper which had been patterned using rubber based ink. The chip was applied for urine of patient, that has analitycal characteristics included response time approximately for 4 hours, linierity of creatinin achieved in concentration range of 0.1 -100 µg/ml and protein of 1 – 200 µg/ml, LOD (limit of detection) and LOQ (limit of quantification) of creatinin 0.088 µg/ml and 0.293 µg/ml, and protein 0.462 µg/ml and 1.540 µg/ml respectively. Interference study showed that urea, salt and sugar, interferen around 0.271-1.966% for creatinin and protein of 0.429 – 1.786%, respectively. The chip could be used up to 3 weeks if it stored in a dry place on room temperature and can be used to analyze condition of CKD over health condition. Keyword: CKD creatinin, protein, pH, and sensor